ANALISIS KARAKTERISTIK PERILAKU MENYIMPANG SISWA KELAS V MADRASAH IBTIDAIYAH (MI) NURUL IHSAN BATURUSA - Said Akhmad Maulana; Muhammad Indera Fisabillillah (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to analyze and understand the characteristics of deviant behavior in the fifth-grade class of Adrasah Ibtidaiyah Nurul Ihsan Baturusa. The research method applied is a qualitative research method through data collection techniques of observation, interviews, and documentation. The data analysis technique used involves pre-field analysis and field analysis. The research findings indicate that the deviant behavior characteristics of fifth-grade students at Madrasah Ibtidaiyah Nurul Ihsan Baturusa include skipping school, lying, stealing, damaging school facilities, fighting, and disobeying teachers' orders.